Investigation of the milk composition of three Tsigai sheep varieties, and the detection of cazein fractions of sheep milk by Reversed-Phase HPLC - Bajúsz, Ildikó (Acta Agraria Debreceniensis, 2008)
The measurements started in 2005, the author used the milk of 3 types of Tsigai Sheep that are suitable for milking, they examined the milk composition, the possible differences between the milk types, the coagulation characteristics, cheese processing, yielding characteristics and the transfer of solid content into cheese. From the large number of measurements, the results of milk composition examinations are described.During the research the author examined the milk coagulation property of three types of Tsigai Sheep QTS 25 is a substance investigating instrument, and its primary mission is the analysis of the substance profile. The advantage of this instrument is the representation of the survey graphs from which the part of the substance characteristics could be directly read off. By the help of the applied mathematical and statistical operations we tried to establish connection between the congealment-hardness and the specialty of the different types of Tsigai Sheep.In 2006 the author began the identification and qualification of the major sheep milk proteins by RP- HPLC method. She used a scientific article written by Bordin et al. The method is able to separate and quantify the seven major proteins. However Bordin’s procedure was developed using bovine milk, the author adapted it to sheep milk.